2014
DOI: 10.1108/ijhma-12-2012-0062
|View full text |Cite
|
Sign up to set email alerts
|

Price effects of surface street traffic on residential property

Abstract: 2011),"Effect of property management on property price: a case study in HK", Facilities, Vol. 29 Iss 11/12 pp. 459-471 http://dx.If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…Using a hedonic price model (HPM), Sander et al (2010) implied that 10% more tree cover on parcels increased sales price by 0.48% in Minnesota. Besides trees, the impacts of other features on the property value, such as open space (Anderson & West, 2006), street lighting (Willis et al, 2005), and surface street traffic (Larsen & Blair, 2014) have been studied separately with the HPM approach.…”
Section: Street Quality and Property Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a hedonic price model (HPM), Sander et al (2010) implied that 10% more tree cover on parcels increased sales price by 0.48% in Minnesota. Besides trees, the impacts of other features on the property value, such as open space (Anderson & West, 2006), street lighting (Willis et al, 2005), and surface street traffic (Larsen & Blair, 2014) have been studied separately with the HPM approach.…”
Section: Street Quality and Property Valuesmentioning
confidence: 99%
“…The hedonic price model (HPM) was widely adopted to investigate the impacts of built environment features on housing prices (Chen et al, 2020;Larsen & Blair, 2014;Zhang & Dong, 2018). It assumes that housing is a heterogeneous good, and the determinants of its price can be investigated by regressing the housing price on three types of independent variables capturing the property's structural, locational and neighborhood attributes (Rosen, The impacts of street environment on pre-owned housing price in Shanghai using street-level images 1974).…”
Section: Hedonic Price Modelmentioning
confidence: 99%
“…Location influence the access of a household to jobs, resources, alongside various social and urban facilities, generating suitable accessibility, but also noise and air pollution caused by vehicles (Baranzini and Schaerer, 2011;Larsen and Blair, 2014;Tian et al, 2017). By using data from Athens, Greece, Efthymiou and Antoniou (2013) revealed that the vicinity to transportation infrastructure show a direct effect on house and apartment purchase prices, as well as rents, namely positive influence related to metro, tram, suburban railway and bus stations, but a negative impact of ISAP (the oldest rail in Greece) and national rail stations, airports and ports.…”
Section: Previous Findings Regarding Transport Infrastructure and Houmentioning
confidence: 99%
“…By using data from Athens, Greece, Efthymiou and Antoniou (2013) revealed that the vicinity to transportation infrastructure show a direct effect on house and apartment purchase prices, as well as rents, namely positive influence related to metro, tram, suburban railway and bus stations, but a negative impact of ISAP (the oldest rail in Greece) and national rail stations, airports and ports. Larsen and Blair (2014) examined Kettering, south-western Ohio and noticed that the value of a detached single-family house settled on an arterial street is less by 7.8 per cent than kindred houses located differently, but multi-unit housing placed adjacent to an arterial street showed a 13.75 percent upper sale price. Mulley et al (2016) highlighted for Brisbane, Australia, that being close to bus rapid transit (BRT) systems adds a premium to the housing price of 0.14%, for every hundred meters closer to the BRT station.…”
Section: Previous Findings Regarding Transport Infrastructure and Houmentioning
confidence: 99%
“…In the existing literature, variables such as density, personal relationships, proximity to schools and other amenities, air and toxic pollution, and traffic-related noise and car accidents have been constantly linked to residential land prices (Enríquez Sierra, Barreto Nieto, Correa Caro, & Campo Robledo, 2013;Glaesener & Caruso, 2015;Hu, Yang, Li, Zhang, & Xu, 2016;Kheir & Portnov, 2016;Larsen & Blair, 2014;Lee, 2015;Wen & Goodman, 2013). For example, in a study investigating factors influencing residential land prices in Tokyo and Kitakyushu, population density, the presence of obnoxious facilities and average elevation were found to be significantly related to urban land prices (Gao & Asami, 2007).…”
Section: Literature Review and Development Of The Hypothesesmentioning
confidence: 99%